(untitled) (Quinto Sol, 2013)
This paper addresses the problem of the professionalization of the military forces of the River Plate state in the first half of the 19th century, analyzing the attempts to establish a particular type of discipline and bureaucratic procedures in combat units that had emerged from a very intense popular mobilization. This problem is studied in two times. The regulations governing the administration of the armies and the kind of administrative tasks that were demanded from each officer will first be analyzed. Then this ideal administrative model imported from Europe will be confronted with the realities of its application, through the study of a particular case: the traumatic attempt to transform the Freedom Dragoons -a unit born from the Banda Oriental rural uprising of 1825- into a Line Cavalry Regiment within the Republican Army which was about to open the war against the Brazil. This modest episode, explored through the memoirs of the officer in charge of the reform, will enable us to shed light on the specific constraints encountered by those officials who spoke on behalf of the State and intended to discipline the forces of a people in arms.